Self-Medication using Chlorpheniramine Maleate in Karanganyar Regency, Central Java, Indonesia - Fathoni, Rifqilya Nurul; Ebtavanny, Tamara Gusti; Yunita, Ema Pristi (Faculty of Medicine, Universitas Padjadjaran, 2024)
Self-medication refers to the use of medications by a person without consulting health professionals and prescription. One of the common drugs used for self-medication is chlorpheniramine maleate (CTM), a drug indicated to relieve symptoms of allergy. However, the lack of knowledge about the indications of CTM leads to its significant misuse. Long-term effects of CTM misuse include heart rate regularity disorder, central nervous system disorders, and even coma. The purpose of this study was to analyze the correlation between sociodemographic factors and the appropriateness of CTM use for self-medication from the perspective of the experience of using CTM for self-medication. This cross-sectional study was performed in Karanganyar Regency, Central Java, Indonesia, from October to November 2022 on 117 respondents sampled randomly using cluster sampling method. A questionnaire that was already proven as valid and reliable was used. Results for the appropriateness of CTM use showed that 95.7% of respondents were in good category, 3.4% were in fair category, and 0.9% were in poor category. The hypothesis tests, which were the Somers’d test and the contingency coefficient, showed no correlation between age (p=0.242), gender (p=0.307), income level (p=0.789), experience (p=0.176), and the appropriate use of CTM for self-medication. However, there is a correlation between education level (p=0.048) and the appropriate use of CTM for self-medication, albeit very weak (r=0.065). Therefore, only the level of education affects the appropriate use of CTM for self-medication.